The Influence of E-Government and M-Passport (Mobile Passport) Service Quality on Passport Applicant Satisfaction Levels - Vivi, Anastasia; Sukmarini, Andi Vita; Djalil, Nur Alim (Journal La Bisecoman, 2024)
The research approach used is quantitative-descriptive. This research was conducted at the Makassar TPI Special Class I Immigration Office with the research subject being passport applicants at the Makassar TPI Special Class I Immigration Office with a sample size of 99 people. Data collection using observation, questionnaires and documentation. Result 1) The effect of E-government service quality on the level of satisfaction of passport applicants. The convenience of the M-Passport (Mobile Passport) application is supported by the dexterity of the employees so as to produce good service quality. This is a perfect combination in producing passport applicant satisfaction at the Makassar TPI Special class I immigration office. 2) The effect of M-Passport (Mobile Passport) on the level of satisfaction of passport applicants. In line with what is felt by customers or passport applicants at Immigration Class I Special TPI Makassar. The effectiveness of the implementation of the M-Passport (Mobile Passport) application program which shows success in encouraging service accountability in Immigration Class I Special TPI Makassar. 3) The effect of E-Government and M-Passport (Mobile Passport) service quality on the level of satisfaction of passport applicants. The success obtained from the quality of E-Government and M-Passport (Mobile Passport) services on the level of customer satisfaction also occurs the same. The success of each variable also had a successful effect when tested simultaneously or together on the satisfaction of passport applicants at Immigration Class I Special TPI Makassar.